Strategi Marketing Public Relatios “Mobil Maung” di PT. Pindad (Persero) - Wira Naufal Ariq; Tresna Wiwitan (Bandung Conference Series: Public Relations, 2022)
Abstract. Entering the era of globalization where the competition is getting sharper, the marketing era has made significant progress with the existence of technology. Especially now that producers are advancing to attract the attention of the public or consumers as much as possible through digital information and digital marketing. In business, there is always competition, change, progress and uncertainty. Seeing the increasingly fierce competition, companies must have a Marketing Public Relations Strategy that is right on target. PT. Pindad (Persero) is a State-Owned Enterprise (BUMN) which is engaged in security and defense. PT. Pindad (Persero) which has also attracted the attention of the public lately is the manufacture of "Mobil Maung" which many people then look at, attracted by its dashing and strong appearance. Therefore, PT. Pindad (Persero) provides a civilian version that can be used not only specifically for the TNI. The purpose of this research is to examine the Push Strategy (Push Strategy), Pull Strategy (Pull Strategy) and Pass Strategy (Influence Strategy) "Mobil Maung" at PT. Pindad (Persero). The research method chosen by the researcher is a descriptive qualitative data study research method. Researchers used data collection techniques through interviews, observation, documentation and literature study. Broadly speaking, there are no obstacles in the implementation of the Three Ways Strategy, but during the Covid-19 pandemic, there were obstacles in the implementation of the Three Ways Strategy. In conclusion, that jThree jWays jStrategy j for marketing public relations strategy “Mobil Maung” at PT. Pindad (Persero) is quite successful. Abstrak. Memasuki di era globalisasi yang persaingannya semakin tajam, era pemasaran yang begitu mengalami kemajuan yang signifikan dengan adanya teknologi. Terlebih saat ini memajukan produsen untuk menarik perhatian publik atau konsumen sebanyak-banyaknya melalui informasi digital dan pemasaran digital. Dalam berbisnis selalu mengalami persaingan, perubahan, kemajuan dan ketidak kepastian. Melihat persaingan yang semakin ketat sehingga perusahaan harus memilki Strategi Marketing Public relations yang tepat sasaran. PT. Pindad (Persero) merupakan perusahaan Badan Usaha Milik Negara (BUMN) yang bergerak di bidang keamanan dan pertahanan. PT. Pindad (Persero) yang juga menarik perhatian masyarakat akhir-akhir ini adalah pembuatan “Mobil Maung” yang kemudian banyak masyarakat melirik, tertarik dikarenakan penampilan yang gagah dan kuat. Oleh karena itu, PT. Pindad (Persero) memyediakan versi sipil yang dapat digunakan tidak hanya khusus untuk TNI. Tujuan dari penelitian ini adalah untuk mengkaji Push Strategy (Strategi Dorong), Pull Strategy (Strategi Tarik) dan Pass Strategy (Strategi Mempengaruhi) “Mobil Maung” di PT. Pindad (Persero). Metode penelitian yang dipilih oleh peneliti ialah metode penelitian studi deskriptif data kualitatif. Peneliti menggunakan teknik pengumpulan data melalui wawancara, observasi, dokumentasi dan studi kepustakaan. Secara garis besar tidak terdapat hambatan dalam penerapan Three Ways Strategy, namun dalam masa pandemi Covid-19 ini mengalami hambatan dalam penerapan Three Ways Strategy. Kesimpulannya, bahwajThree jWays jStrategy juntuk strategi marketing public relations“ Mobil Maung” di PT. Pindad (Persero) cukup berhasil